Light and temperature induce variations in the density and ultrastructure of the secretory spaces in the diesel-tree (Copaifera langsdorffii Desf.-Leguminosae) - Rodrigues, T. M. [UNESP]; Buarque, P. F. S. M. [UNESP]; Coneglian, A. G. [UNESP]; Reis, D. C. [UNESP] (Springer, 2014)
This manuscript shows experimentally that light and temperature significantly influence the density and cellular features of the secretory spaces in C . langsdorffii , an economically important legume tree in Brazil.Copaifera langsdorffii is known for its production of terpenes, which are exploited by several industrial sectors. In this species, secretory cavities and canals are present in seedlings and adult plants and constitute an important defense mechanism against herbivores and pathogens. Evidence suggests that exogenous factors modify the production of secretions in this species; however, the influence of these factors on the secretory system structure is unknown. We investigated the effects of light and temperature on the density of secretory canals and cavities in C. langsdorffii seedlings, and the influence of temperature on the ultrastructure of the epithelial cells. Seedlings were maintained in different light intensities (460, 230, and 46 mu mol m(-2) s(-1)) and temperatures (15, 25, and 35 A degrees C) in 3 x 3 combinations. The densities of secretory spaces in epicotyls and eophylls were calculated in cross sections under a light microscope. For ultrastructural studies, samples of eophylls were prepared following the conventional techniques of transmission electron microscopy. Seedlings at 25 A degrees C/230 mu mol m(-2) s(-1) and 25 A degrees C/460 mu mol m(-2) s(-1) showed increased density of cavities and canals, respectively, suggesting an improved protection of the plants in these conditions. Ultrastructurally, the epithelial cells of seedlings observed at 25 A degrees C contained dense cytoplasm rich in organelles, indicating intense secretory activity. At 15 and 35 A degrees C, seedlings showed morphological alterations in mitochondria, plastids, and endoplasmic reticulum. The epithelial cells presented signs of intense lysing at 35 A degrees C, indicating impaired secretory activity. Our data proved that light and temperature can induce alterations in the secretory system of C. langsdorffii seedlings, suggesting changes to their defense system.
Keywords: Anatomy; Cell ultrastructure; Copaiba; Experimental conditions; Secretory canals and cavities